Trevor Schmidt Retells Tales from the Hospital: A Postmodern Theatrical Experience - Kerr, Rosalind (Theatre Research in Canada / Recherches théâtrales au Canada, 2001)
This paper explores the 1998 Edmonton production of Tales from the Hospital, a new work comprised of four monologues by two employees and two inmates of a large, long-term care institution that bears certain resemblances to real life stories of medical experiments and sterilization practised on unfortunate inmates under the Albertan Protection of Life Act that was in place between 1928 and 1973. Timely because many of these individuals are still in the process of seeking compensation, Tales offers a powerful political message, implicating spectators in the power/knowledge systems that allowed such places to function. Through stage design that requires spectators to move from site to site, various narrative devices, and the gestic handling of hospital linens, spectators found themselves involved in the production of not only the theatrical, but also the wider political meanings of the event. Cet article explore la production de Tales from the Hospital faite en 1998 à Edmonton. Cette nouvelle oeuvre consiste de quatre monologues de deux employés et de deux patients d'une institution de soins prolongés. Les histoires racontées mettent en cause des similitudes frappantes et les faits vécus par ces malheureux patients, victimes d'expériences médicales et de stérilisations, pratiquées entre 1928 et 1973 sous la loi albertaine de la protection de la vie (Albertan Protection of Life Act). Tales from the Hospital nous offre un puissant message politique qui est très actuel, puisque plusieurs de ces victimes sont encore à la recherche d'une compensation. En critiquant le système politique qui empêchait les connaissances publiques, ce qui permettait le fonctionnement de ces endroits, la pièce implique ses spectateurs dans un sens direct. À travers de plusieurs stratégies, comme une conception du décor qui exige aux spectateurs de circuler dans l'espace, les approches différentes de narration employées dans la pièce, les gestes de la manutention d'équipements hospitaliers, le publique non seulement assiste à la pièce, mais aussi se trouve impliqué politiquement à cet événement.